Note on the temperature Sombor index - Gutman, Ivan (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The temperature of a vertex of a graph of the order n is defined as d/(n-d), where d is the vertex degree. The temperature variant of the Sombor index is investigated and several of its properties established.Methods: Combinatorial graph theory is applied.Results: Extremal values and bounds for the temperature Sombor index are obtained.Conclusion: The paper contributes to the theory of Sombor-index-like graph invariants.
Keywords: temperature (of vertex); temperature vertex-degree-based graph invariant; Sombor index; temperature Sombor index